The impact of learning to read on visual processing - Regine Kolinsky (Frontiers Research Topics, 2016)
Reading is at the interface between the vision and spoken language domains. An emergent bulk of research indicates that learning to read strongly impacts on non-linguistic visual object processing, both at the behavioral level (e.g., on mirror image processing - enantiomorphy) and at the brain level (e.g., inducing top-down effects as well as neural competition effects). Yet, many questions regarding the exact nature, locus, and consequences of these effects remain hitherto unanswered. The current Special Topic aims at contributing to the understanding of how such a cultural activity as reading might modulate visual processing by providing a landmark forum in which researchers define the state of the art and future directions on this issue. We thus welcome reviews of current work, original research, and opinion articles that focus on the impact of literacy on the cognitive and/or brain visual processes. In addition to studies directly focusing on this topic, we will consider as highly relevant evidence on reading and visual processes in typical and atypical development, including in adult people differing in schooling and literacy, as well as in neuropsychological cases (e.g., developmental dyslexia). We also encourage researchers on nonhuman primate visual processing to consider the potential contribution of their studies to this Special Topic.